The wealth of a visit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In Malawi, there is a vernacular proverb that 'Knowledge is wealth'. Agroforestry workers from eastern and southern Africa went to Malawi and Zambia in January looking for that wealth, and they found it. It was at the end of an intensive two-week...